SPECTROPHOTOMETRIC ANN ATOMIC ABSORPTION DETERMINATION CEFIXIME BY CLOUD POINT EXTRACTION IN PURE FORM - & Mohammed, Dhahir (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
A simple, rapid, accurate, sensitive and ecofriendly method has been developed for the quantitative determination of Cefixime (CFX) in pure form and pharmaceutical preparations by using a combination of cloud point extraction with UV-Visible absorption spectrophotometric method. Analytical applications of complexation with metal ions by reacting Cefixime (CFX) with Iron (III) to form chelate complexes under limited experimental conditions. The method based to dissolved CFX in 0.1 M NaOH, 10% (v/v) Triton X-114 and mixed with (1000 μg mL-1 ) Iron (III). The formation of CFX- Fe (III) complex was formatted at pH 11 and wavelength at 439 nm. The complex of CFX- Fe (III) obey Beer’s Law in the range 10-160μg/ml. LOD and LOQ values for the complex were 1.5865 μg/ml and 5.2887 μg/ml respectively. Method was validated and successfully applied to drug formulations like syrup infusion The results of analysis have been validated statistically and by recovery studies and were found satisfactory.